Adsorption resin and preparation method thereof and method for removing additives from plating solution
The adsorbent resin prepared by embedding modified activated carbon and crosslinking resins solves the waste problem caused by the replacement of additives in the plating solution, and achieves efficient removal of additives and organic waste in the plating solution, reduces production costs, and is characterized by easy regeneration.
Patent Information
- Application Number
- CN202411231387.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-09-04
AI Technical Summary
In the production of semi-gloss nickel and bright nickel products, the replacement of additives in the plating solution leads to waste of plating solution, increasing production costs.
Adsorption resin is used to prepare an adsorption resin with high mechanical strength, hydrophobic surface and regulatory pore structure by embedding modified activated carbon and crosslinking resin, and is used to remove additives and organic waste in the plating solution.
It realizes efficient removal of additives and organic waste in the plating solution, reduces the frequency of plating solution replacement, reduces production costs, and is easy to regenerate adsorbed resin, with broad application prospects.
Smart Images

Figure BDA0005026242260000141 
Figure BDA0005026242260000151 
Figure BDA0005026242260000161
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electroplating, and in particular to an adsorption resin and a preparation method thereof, and a method for removing additives from a plating solution. Background Art
[0002] When producing semi-bright nickel products or bright nickel products, additives such as brighteners or wetting agents need to be added to the plating solution during production to ensure the uniformity, dispersion and stability of the products. Since different products require different additives, the entire plating solution needs to be replaced when the additives are replaced. However, since the cost of the plating solution itself is relatively high, replacement will cause waste. Therefore, a technology that can remove additives is designed and developed. When replacing additives, the additives in the plating solution are directly removed through the plating solution circulation, and then new additives are added to continue production. During the process, the plating solution does not need to be replaced, which can greatly reduce costs. At the same time, organic waste in the plating solution can also be removed during the process of removing additives. Summary of the invention
[0003] The purpose of the present invention is to provide an adsorption resin and a preparation method thereof and a method for removing additives from a plating solution. The adsorption resin is used for removal. The adsorption resin has the advantages of higher mechanical strength, a more hydrophobic surface, and an adjustable pore structure, and has better adsorption properties for organic matter, but almost no adsorption for metal ions. Compared with ordinary activated carbon, it reduces the loss of metal ions, is easy to regenerate, and reduces costs, thereby having broad application prospects.
[0004] The technical solution of the present invention is achieved in this way:
[0005] The present invention provides a method for preparing an adsorption resin, comprising the following steps:
[0006] S1. Modification of activated carbon: After ball milling the activated carbon, add it to ethanol, add long-chain silane, heat and stir to react, filter, wash, and dry to obtain modified activated carbon;
[0007] S2. Low-crosslinked resin embedded activated carbon: the modified activated carbon obtained in step S1, styrene, divinylbenzene, toluene, porogen and initiator are mixed evenly to obtain an oil phase, gelatin and methylene blue are added to water to obtain an aqueous phase; under the protection of inert gas, the oil phase is added to the aqueous phase, heated and stirred to react, filtered, washed and dried to obtain low-crosslinked styrene-styrene copolymer embedded activated carbon;
[0008] S3 chlorination: chloromethyl ether and the low cross-linked styrene - diphenylethylene copolymer embedded activated carbon prepared in step S2 were added to dichloromethane, zinc chloride catalyst was added, the reaction was heated with stirring, filtered, washed, and dried to obtain a chlorinated low cross-linked styrene - diphenylethylene copolymer embedded activated carbon;
[0009] S4. Re-crosslinking: The chlorinated low cross-linked styrene-styrene copolymer embedded activated carbon obtained in step S3 was added to ethylene dichloride, a catalyst of ferric chloride was added, the reaction was heated with stirring, filtered, washed, and dried to obtain a highly cross-linked styrene-styrene copolymer embedded activated carbon;
[0010] S5. Ultra-high crosslinking: Add the highly crosslinked styrene-styrene copolymer embedded activated carbon obtained in step S4 into dichloroethane, add chloromethyl ether, fully swell, cool, add catalyst tin tetrachloride, keep warm, heat up and react with crosslinking to obtain an adsorption resin.
[0011] As a further improvement of the present invention, the ball milling time in step S1 is 1-3 hours, the mass ratio of the activated carbon and the long-chain alkyl silane is 10:2-3, the long-chain silane is selected from at least one of hexadecyltrimethoxysilane, n-decyltrimethoxysilane, dodecyltrimethoxysilane, and dodecylmethyldimethoxysilane, and the temperature of the heating and stirring reaction is 35-45°C, and the time is 2-3 hours.
[0012] As a further improvement of the present invention, the mass ratio of the modified activated carbon, styrene, divinylbenzene, toluene, porogen and initiator in step S2 is 10:4-6:5-7:10-12:0.2-0.3:0.01-0.02, the mass ratio of gelatin and methylene blue is 2-4:0.01-0.02, and the heating and stirring reaction method is: keeping warm and stirring the reaction at 70-80°C for 2-3h, keeping warm and stirring the reaction at 80-90°C for 4-6h, and keeping warm and stirring the reaction at 90-100°C for 3-5h.
[0013] Preferably, the porogen is selected from at least one of chlorodecane or xylene.
[0014] As a further improvement of the present invention, in step S3, the mass ratio of chloromethyl ether, low-crosslinked styrene-styrene copolymer embedded activated carbon, and catalyst zinc chloride is 1.8-2.5:10:0.01-0.02, and the temperature of the heating and stirring reaction is 30-40°C, and the time is 3-5h.
[0015] As a further improvement of the present invention, in step S4, the mass ratio of the chlorinated low-crosslinked styrene-styrene copolymer embedded activated carbon to the catalyst ferric chloride is 100:0.5-1, and the stirring reaction time is 5-7h.
[0016] As a further improvement of the present invention, in step S5, the mass ratio of the highly cross-linked styrene-styrene copolymer embedded activated carbon, chloromethyl ether, and catalyst tin tetrachloride is 20-30:3-4:0.01-0.02, the cooling to 4-8°C, the swelling time is 1-3h, the insulation treatment time is 0.5-1.5h, the temperature of the heating cross-linking reaction is 75-85°C, and the time is 10-12h.
[0017] Preferably, a method for preparing an adsorption resin comprises the following steps:
[0018] S1. Modification of activated carbon: After ball milling 10 parts by weight of activated carbon for 1-3 hours, add it to ethanol, add 2-3 parts by weight of long-chain silane, heat to 35-45°C, stir and react for 2-3 hours, filter, wash and dry to obtain modified activated carbon;
[0019] S2. Low cross-linked resin embedded activated carbon: 10 parts by weight of the modified activated carbon obtained in step S1, 4-6 parts by weight of styrene, 5-7 parts by weight of divinylbenzene, 10-12 parts by weight of toluene, 0.2-0.3 parts by weight of a porogen and 0.01-0.02 parts by weight of an initiator are mixed evenly to obtain an oil phase, 2-4 parts by weight of gelatin and 0.01-0.02 parts by weight of methylene blue are added to 100 parts by weight of water to obtain an aqueous phase; under the protection of an inert gas, the oil phase is added dropwise to the aqueous phase, the mixture is stirred at 70-80°C for 2-3h, stirred at 80-90°C for 4-6h, and stirred at 90-100°C for 3-5h, filtered, washed, and dried to obtain low cross-linked styrene-styrene copolymer embedded activated carbon;
[0020] S3. Chlorination: 1.8-2.5 parts by weight of chloromethyl ether and 10 parts by weight of the low cross-linked styrene-styrene copolymer-embedded activated carbon prepared in step S2 were added to dichloromethane, swollen for 2 hours, 0.01-0.02 parts by weight of zinc chloride catalyst was added, heated to 30-40 ° C, stirred for 3-5 hours, filtered, washed, and dried to obtain a chlorinated low cross-linked styrene-styrene copolymer-embedded activated carbon;
[0021] S4. Re-crosslinking: 100 parts by weight of the chlorinated low-crosslinked styrene-styrene copolymer embedded activated carbon prepared in step S3 was added to ethylene dichloride, swollen, 0.5-1 parts by weight of ferric chloride catalyst was added, heated to reflux, stirred for 5-7h, filtered, washed, and dried to obtain a highly crosslinked styrene-styrene copolymer embedded activated carbon;
[0022] S5. Ultra-high crosslinking: Add 20-30 parts by weight of the highly crosslinked styrene-styrene copolymer embedded activated carbon obtained in step S4 to dichloroethane, add 3-4 parts by weight of chloromethyl ether, swell for 1-3 hours, cool to 4-8°C, add 0.01-0.02 parts by weight of catalyst tin tetrachloride, keep warm for 0.5-1.5 hours, heat to 75-85°C, crosslink for 10-12 hours to obtain an adsorption resin.
[0023] The present invention further protects an adsorption resin obtained by the above preparation method.
[0024] The present invention further protects a method for removing additives from a plating solution, which comprises filling the above-mentioned adsorption resin onto an adsorption column, circulating the plating solution through the adsorption column, and when the detected content of the additive in the plating solution is lower than a maximum value, stopping the circulation, collecting the plating solution from which the additive has been removed, taking out the adsorption column, and regenerating the adsorbed adsorption resin therein for recycling.
[0025] The present invention further protects a method for regenerating an adsorption resin, wherein the adsorption resin after adsorption is added to a treatment solution, compressed air is introduced into the solution, and ultrasonic treatment, filtration, washing and drying are performed simultaneously to obtain a regenerated adsorption resin.
[0026] As a further improvement of the present invention, the treatment solution is an ethanol aqueous solution containing 8-10wt% hydrochloric acid or NaOH, wherein the ethanol content is 40-60wt%, the ventilation volume of the compressed air is 10-20mL / min, the power of the ultrasonic treatment is 1000-2000W, and the time is 0.5-1.5h.
[0027] The present invention has the following beneficial effects:
[0028] The present invention prepares a special porous structure of adsorption resin microspheres, which show strong affinity to macromolecular organic matter and are mainly used to remove organic additives in plating solutions, such as benzene, aniline and their derivatives, so as to achieve the purpose of purification.
[0029] The present invention uses activated carbon as a core, which contains a rich porous structure and can absorb a large amount of organic matter, greatly improving the adsorption capacity of the microspheres; the surface is modified by long-chain alkyl to make the surface of the activated carbon hydrophobic, and styrene and divinylbenzene monomers can be coated and cross-linked on the surface by suspension polymerization. Under the action of a porogen, the cross-linked structure presents pores of different sizes, and after further chlorination, Friedel-Crafts alkylation reaction occurs under the action of a catalyst, so that the cross-linking degree is increased, and highly cross-linked styrene-styrene copolymer embedded activated carbon is obtained. However, there are still some sites on the resin structure that can be cross-linked, so it is chlorinated again with chloromethyl ether, and further cross-linking occurs under the action of a high-efficiency catalyst, thereby obtaining an ultra-high cross-linked microsphere material.
[0030] The ultra-high cross-linked microsphere material prepared by the present invention not only has a very high specific surface area and abundant micropores, but also has the advantages of higher mechanical strength, more hydrophobic surface, adjustable pore structure, etc. compared with pure activated carbon, and has better adsorption characteristics for organic matter, and almost no adsorption for metal ions. Compared with ordinary activated carbon, it reduces the loss of metal ions and reduces the cost of purification. Moreover, after ultra-high cross-linking, it can prevent the expansion of the network structure after solvent desorption, is stable to heat and chemicals and easy to regenerate, and can be recycled, thereby further reducing costs and facilitating industrial application. At the same time, the ultra-high cross-linked microsphere material adopts multiple cross-linking reactions, and the pores of the prepared material are similar to the size of the organic matter in the plating solution, which can selectively adsorb a large amount of organic matter and improve the adsorption efficiency;
[0031] The ultra-high cross-linked microsphere material prepared by the present invention uses polyvinylbenzene as a cross-linking monomer, and its large π bond can selectively separate aromatic additives such as benzene and aniline and organic waste in the plating solution through π-π conjugation, while it has low adsorption capacity for other active components such as metal ions, so it can selectively adsorb and remove components such as organic additives and organic waste, thereby achieving the removal and purification of some components in the plating solution.
[0032] After the ultra-high cross-linked microsphere material of the present invention is adsorbed, efficient regeneration can be achieved through a simple treatment method. The acid or alkali is dissolved in an ethanol aqueous solution, the analysis effect is good, the resin reuse rate is high, the adsorbate is salted in the acid and alkali solution, and is well analyzed from the resin. At the same time, the impact on the life of the resin is relatively small, the analysis rate is high, and the adsorbate can be oxidized by passing air, and analyzed under ultrasonic treatment to enter the solution, thereby achieving efficient regeneration of the resin material, allowing the resin to be recycled and reducing costs.
[0033] The method for removing additives from the plating solution of the present invention adopts adsorption resin for removal. The adsorption resin has the advantages of higher mechanical strength, more hydrophobic surface, adjustable pore structure, better adsorption characteristics for organic matter, and almost no adsorption for metal ions. Compared with ordinary activated carbon, it reduces the loss of metal ions, is easy to regenerate, and reduces costs, thereby having broad application prospects. DETAILED DESCRIPTION
[0034] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Example 1
[0036] This embodiment provides a method for preparing an adsorption resin, comprising the following steps:
[0037] S1. Modification of activated carbon: After ball milling 10 g of activated carbon for 1 h, add it to 100 mL of ethanol, add 2 g of hexadecyltrimethoxysilane, heat to 35 ° C, stir and react for 2 h, filter, wash, and dry to obtain modified activated carbon;
[0038] S2. Low-crosslinked resin-embedded activated carbon: 10 g of the modified activated carbon obtained in step S1, 4 g of styrene, 5 g of divinylbenzene, 10 g of toluene, 0.2 g of chlorodecane and 0.01 g of benzoyl peroxide were mixed evenly to obtain an oil phase, 2 g of gelatin and 0.01 g of methylene blue were added to 100 mL of water to obtain an aqueous phase; under nitrogen protection, the oil phase was added dropwise to the aqueous phase, and the mixture was stirred at 70°C for 2 h, at 80°C for 4 h, and at 90°C for 3 h, filtered, washed, and dried to obtain low-crosslinked styrene-styrene copolymer-embedded activated carbon;
[0039] S3. Chlorination: 1.8 g of chloromethyl ether and 10 g of the low cross-linked styrene-styrene copolymer-embedded activated carbon prepared in step S2 were added to 100 mL of dichloromethane, swollen for 2 h, 0.01 g of zinc chloride catalyst was added, heated to 30 ° C, stirred for 3 h, filtered, washed, and dried to obtain a chlorinated low cross-linked styrene-styrene copolymer-embedded activated carbon;
[0040] S4. Re-crosslinking: 100 g of the chlorinated low-crosslinked styrene-styrene copolymer embedded activated carbon prepared in step S3 was added to 500 mL of ethylene dichloride, swollen for 1 h, 0.5 g of the catalyst ferric chloride was added, heated to reflux, stirred for 5 h, filtered, washed, and dried to obtain a highly crosslinked styrene-styrene copolymer embedded activated carbon;
[0041] S5. Ultra-high crosslinking: Add 20 g of the highly crosslinked styrene-styrene copolymer embedded activated carbon prepared in step S4 into 200 mL of dichloroethane, add 3 g of chloromethyl ether, swell for 1 hour, cool to 4°C, add 0.01 g of catalyst tin tetrachloride, keep warm for 0.5 hour, heat to 75°C, crosslink for 10 hours to obtain the adsorption resin.
[0042] Example 2
[0043] This embodiment provides a method for preparing an adsorption resin, comprising the following steps:
[0044] S1. Modification of activated carbon: After ball milling 10 g of activated carbon for 3 h, add it to 100 mL of ethanol, add 3 g of n-decyltrimethoxysilane, heat to 45 ° C, stir and react for 3 h, filter, wash, and dry to obtain modified activated carbon;
[0045] S2. Low-crosslinked resin-embedded activated carbon: 10 g of the modified activated carbon obtained in step S1, 6 g of styrene, 7 g of divinylbenzene, 12 g of toluene, 0.3 g of chlorodecane and 0.02 g of benzoyl peroxide were mixed evenly to obtain an oil phase, 4 g of gelatin and 0.02 g of methylene blue were added to 100 mL of water to obtain an aqueous phase; under nitrogen protection, the oil phase was added dropwise to the aqueous phase, and the mixture was stirred at 80°C for 3 h, at 90°C for 6 h, and at 100°C for 5 h, filtered, washed, and dried to obtain low-crosslinked styrene-styrene copolymer-embedded activated carbon;
[0046] S3. Chlorination: 2.5 g of chloromethyl ether and 10 g of the low cross-linked styrene-styrene copolymer-embedded activated carbon prepared in step S2 were added to 100 mL of dichloromethane, swollen for 2 h, 0.02 g of zinc chloride catalyst was added, heated to 40 ° C, stirred for 5 h, filtered, washed, and dried to obtain a chlorinated low cross-linked styrene-styrene copolymer-embedded activated carbon;
[0047] S4. Re-crosslinking: 100 g of the chlorinated low-crosslinked styrene-styrene copolymer embedded activated carbon prepared in step S3 was added to 500 mL of ethylene dichloride, swollen for 1 h, 1 g of catalyst ferric chloride was added, heated to reflux, stirred for 7 h, filtered, washed, and dried to obtain a highly crosslinked styrene-styrene copolymer embedded activated carbon;
[0048] S5. Ultra-high crosslinking: Add 30 g of the highly crosslinked styrene-styrene copolymer embedded activated carbon prepared in step S4 into 200 mL of dichloroethane, add 4 g of chloromethyl ether, swell for 3 h, cool to 8°C, add 0.02 g of catalyst tin tetrachloride, keep warm for 1.5 h, heat to 85°C, crosslink for 12 h to obtain the adsorption resin.
[0049] Example 3
[0050] This embodiment provides a method for preparing an adsorption resin, comprising the following steps:
[0051] S1. Modification of activated carbon: After ball milling 10 g of activated carbon for 2 h, add it to 100 mL of ethanol, add 2.5 g of dodecylmethyldimethoxysilane, heat to 40 ° C, stir and react for 2.5 h, filter, wash, and dry to obtain modified activated carbon;
[0052] S2. Low-crosslinked resin-embedded activated carbon: 10 g of the modified activated carbon obtained in step S1, 5 g of styrene, 6 g of divinylbenzene, 11 g of toluene, 0.25 g of xylene and 0.015 g of benzoyl peroxide were mixed evenly to obtain an oil phase, 3 g of gelatin and 0.015 g of methylene blue were added to 100 mL of water to obtain an aqueous phase; under nitrogen protection, the oil phase was added dropwise to the aqueous phase, and the mixture was stirred at 75°C for 2.5 h, at 85°C for 5 h, and at 95°C for 4 h, filtered, washed, and dried to obtain low-crosslinked styrene-styrene copolymer-embedded activated carbon;
[0053] S3. Chlorination: 2.1 g of chloromethyl ether and 10 g of the low cross-linked styrene-styrene copolymer-embedded activated carbon prepared in step S2 were added to 100 mL of dichloromethane, swollen for 2 h, 0.015 g of zinc chloride catalyst was added, heated to 35 ° C, stirred for 4 h, filtered, washed, and dried to obtain a chlorinated low cross-linked styrene-styrene copolymer-embedded activated carbon;
[0054] S4. Re-crosslinking: 100 g of the chlorinated low-crosslinked styrene-styrene copolymer embedded activated carbon prepared in step S3 was added to 500 mL of ethylene dichloride, swollen for 1 h, 0.7 g of catalyst ferric chloride was added, heated to reflux, stirred for 6 h, filtered, washed, and dried to obtain a highly crosslinked styrene-styrene copolymer embedded activated carbon;
[0055] S5. Ultra-high crosslinking: Add 25 g of the highly crosslinked styrene-styrene copolymer embedded activated carbon obtained in step S4 into 200 mL of dichloroethane, add 3.4 g of chloromethyl ether, swell for 2 hours, cool to 6°C, add 0.015 g of catalyst tin tetrachloride, keep warm for 1 hour, heat to 80°C, crosslink for 11 hours to obtain the adsorption resin.
[0056] Comparative Example 1
[0057] Compared with Example 3, the difference is that step S1 is not performed.
[0058] The details are as follows:
[0059] S1. Low cross-linked resin embedded activated carbon: 10g activated carbon, 5g styrene, 6g divinylbenzene, 11g toluene, 0.25g xylene and 0.015g benzoyl peroxide were mixed evenly to obtain an oil phase, 3g gelatin and 0.015g methylene blue were added to 100mL water to obtain an aqueous phase; under nitrogen protection, the oil phase was added dropwise to the aqueous phase, and the mixture was stirred at 75°C for 2.5h, at 85°C for 5h, and at 95°C for 4h, filtered, washed and dried to obtain low cross-linked styrene-styrene copolymer embedded activated carbon;
[0060] S2. Chlorination: 2.1 g of chloromethyl ether and 10 g of the low cross-linked styrene-styrene copolymer-embedded activated carbon prepared in step S1 were added to 100 mL of dichloromethane, swollen for 2 h, 0.015 g of zinc chloride catalyst was added, heated to 35 ° C, stirred for 4 h, filtered, washed, and dried to obtain a chlorinated low cross-linked styrene-styrene copolymer-embedded activated carbon;
[0061] S3. Re-crosslinking: 100 g of the chlorinated low-crosslinked styrene-styrene copolymer embedded activated carbon prepared in step S2 was added to 500 mL of ethylene dichloride, swollen for 1 h, 0.7 g of catalyst ferric chloride was added, heated to reflux, stirred for 6 h, filtered, washed, and dried to obtain a highly crosslinked styrene-styrene copolymer embedded activated carbon;
[0062] S4. Ultra-high crosslinking: Add 25 g of the highly crosslinked styrene-styrene copolymer embedded activated carbon obtained in step S3 into 200 mL of dichloroethane, add 3.4 g of chloromethyl ether, swell for 2 hours, cool to 6°C, add 0.015 g of catalyst tin tetrachloride, keep warm for 1 hour, heat to 80°C, and crosslink for 11 hours to obtain the adsorption resin.
[0063] Comparative Example 2
[0064] Compared with Example 3, the difference is that no modified activated carbon is added in step S2.
[0065] The details are as follows:
[0066] S1. Preparation of low cross-linked resin microspheres: 5 g styrene, 6 g divinylbenzene, 11 g toluene, 0.25 g xylene and 0.015 g benzoyl peroxide were mixed uniformly to obtain an oil phase, 3 g gelatin, 10 g talcum powder and 0.015 g methylene blue were added to 100 mL water to obtain an aqueous phase; under nitrogen protection, the oil phase was added dropwise to the aqueous phase, and the mixture was stirred at 75°C for 2.5 h, at 85°C for 5 h, and at 95°C for 4 h, filtered, washed and dried to obtain low cross-linked styrene-styrene copolymer resin microspheres;
[0067] S2. Chlorination: 2.1 g of chloromethyl ether and 10 g of the low cross-linked styrene-styrene copolymer resin microspheres prepared in step S1 were added to 100 mL of dichloromethane, swollen for 2 h, 0.015 g of zinc chloride catalyst was added, heated to 35 ° C, stirred for 4 h, filtered, washed, and dried to obtain chlorinated low cross-linked styrene-styrene copolymer resin microspheres;
[0068] S3. Re-crosslinking: 100 g of the chlorinated low-crosslinked styrene-styrene copolymer resin microspheres obtained in step S2 were added to 500 mL of dichloroethane, swollen for 1 h, 0.7 g of ferric chloride catalyst was added, heated to reflux, stirred for 6 h, filtered, washed, and dried to obtain highly crosslinked styrene-styrene copolymer resin microspheres;
[0069] S4. Ultra-high crosslinking: Add 25 g of the highly crosslinked styrene-styrene copolymer resin microspheres obtained in step S3 to 200 mL of dichloroethane, add 3.4 g of chloromethyl ether, swell for 2 h, cool to 6 ° C, add 0.015 g of catalyst tin tetrachloride, keep warm for 1 h, heat to 80 ° C, crosslink for 11 h to obtain an adsorption resin.
[0070] Comparative Example 3
[0071] Compared with Example 3, the difference is that steps S3 to S5 are not performed.
[0072] The details are as follows:
[0073] S1. Modification of activated carbon: After ball milling 10 g of activated carbon for 2 h, add it to 100 mL of ethanol, add 2.5 g of dodecylmethyldimethoxysilane, heat to 40 ° C, stir and react for 2.5 h, filter, wash, and dry to obtain modified activated carbon;
[0074] S2. Low-crosslinked resin-encapsulated activated carbon: evenly mix 10 g of the modified activated carbon obtained in step S1, 5 g of styrene, 6 g of divinylbenzene, 11 g of toluene, 0.25 g of xylene and 0.015 g of benzoyl peroxide to obtain an oil phase, add 3 g of gelatin and 0.015 g of methylene blue into 100 mL of water to obtain an aqueous phase; under nitrogen protection, dropwise add the oil phase into the aqueous phase, heat and stir at 75°C for 2.5 h, heat and stir at 85°C for 5 h, heat and stir at 95°C for 4 h, filter, wash and dry to obtain low-crosslinked styrene-styrene copolymer-encapsulated activated carbon, which is the adsorption resin.
[0075] Comparative Example 4
[0076] Compared with Embodiment 3, the difference is that step S5 is not performed.
[0077] The details are as follows:
[0078] S1. Modification of activated carbon: After ball milling 10 g of activated carbon for 2 h, add it to 100 mL of ethanol, add 2.5 g of dodecylmethyldimethoxysilane, heat to 40 ° C, stir and react for 2.5 h, filter, wash, and dry to obtain modified activated carbon;
[0079] S2. Low-crosslinked resin-embedded activated carbon: 10 g of the modified activated carbon obtained in step S1, 5 g of styrene, 6 g of divinylbenzene, 11 g of toluene, 0.25 g of xylene and 0.015 g of benzoyl peroxide were mixed evenly to obtain an oil phase, 3 g of gelatin and 0.015 g of methylene blue were added to 100 mL of water to obtain an aqueous phase; under nitrogen protection, the oil phase was added dropwise to the aqueous phase, and the mixture was stirred at 75°C for 2.5 h, at 85°C for 5 h, and at 95°C for 4 h, filtered, washed, and dried to obtain low-crosslinked styrene-styrene copolymer-embedded activated carbon;
[0080] S3. Chlorination: 2.1 g of chloromethyl ether and 10 g of the low cross-linked styrene-styrene copolymer-embedded activated carbon prepared in step S2 were added to 100 mL of dichloromethane, swollen for 2 h, 0.015 g of zinc chloride catalyst was added, heated to 35 ° C, stirred for 4 h, filtered, washed, and dried to obtain a chlorinated low cross-linked styrene-styrene copolymer-embedded activated carbon;
[0081] S4. Re-crosslinking: Add 100 g of the chlorinated low-crosslinked styrene-styrene copolymer embedded activated carbon obtained in step S3 into 500 mL of dichloroethane, swell for 1 hour, add 0.7 g of catalyst ferric chloride, heat to reflux, stir and react for 6 hours, filter, wash, and dry to obtain highly crosslinked styrene-styrene copolymer embedded activated carbon, which is the adsorption resin.
[0082] Comparative Example 5
[0083] Compared with Example 3, the difference is that modified activated carbon is not added in step S2 and step S5 is not performed.
[0084] The details are as follows:
[0085] S1. Preparation of low cross-linked resin balls: 5 g styrene, 6 g divinylbenzene, 11 g toluene, 0.25 g xylene and 0.015 g benzoyl peroxide were mixed uniformly to obtain an oil phase, 3 g gelatin, 10 g talcum powder and 0.015 g methylene blue were added to 100 mL water to obtain an aqueous phase; under nitrogen protection, the oil phase was added dropwise to the aqueous phase, and the mixture was stirred at 75° C. for 2.5 h, at 85° C. for 5 h, and at 95° C. for 4 h, filtered, washed and dried to obtain low cross-linked styrene-styrene copolymer resin balls;
[0086] S2. Chlorination: 2.1 g of chloromethyl ether and 10 g of the low cross-linked styrene-styrene copolymer resin balls obtained in step S1 were added to 100 mL of dichloromethane, swollen for 2 h, 0.015 g of zinc chloride catalyst was added, heated to 35 ° C, stirred for 4 h, filtered, washed, and dried to obtain chlorinated low cross-linked styrene-styrene copolymer resin balls;
[0087] S3. Re-crosslinking: Add 100 g of the chlorinated low-crosslinked styrene-styrene copolymer resin balls obtained in step S2 into 500 mL of dichloroethane, swell for 1 hour, add 0.7 g of catalyst ferric chloride, heat to reflux, stir and react for 6 hours, filter, wash, and dry to obtain highly crosslinked styrene-styrene copolymer resin balls, which are the adsorption resin.
[0088] Test Example 1
[0089] The adsorption resins prepared in Examples 1-3 and Comparative Examples 1-5 were characterized using an ASAP2010 N2-physical adsorption instrument (Micromeritics, USA). The specific surface area was calculated using the Brunauer-Emmett-Teller (BET) formula, and the pore volume was calculated using the Dubinin-Radushkevich (DR) and Barrett-Joyner-Halena (BJH) methods. The results are shown in Table 1.
[0090] Table 1
[0091]
[0092] It can be seen from the above table that the adsorption resins prepared in Examples 1-3 of the present invention have a large specific surface area and a rich pore structure.
[0093] Test Example 2
[0094] Weigh 0.1 g of each of the adsorption resins prepared in Examples 1-3 and Comparative Examples 1-5 into a conical flask, add 100 ml of an adsorbate solution (benzene and aniline) with an initial concentration of 1 mol / L. Oscillate in a constant temperature oscillator at 288 K and 303 K for more than 24 hours to ensure that adsorption equilibrium is reached. Take 0.01 ml of the equilibrium solution and analyze the equilibrium concentration C using HPLC. e .
[0095] Equilibrium adsorption capacity Q e =(C0-C e )V / MW
[0096] Where Q e is the equilibrium adsorption capacity (mmol / g), C0 and C e are the concentrations of the original solution and the equilibrium solution (mg / L), V is the volume of the solution (L), W is the mass of the resin (g), and M is the relative molecular mass of the adsorbate molecule.
[0097] The results are shown in Table 2.
[0098] Table 2
[0099]
[0100] It can be seen from the above table that the adsorption resins prepared in Examples 1-3 of the present invention have good adsorption effects on benzene and aniline.
[0101] Example 4
[0102] This embodiment provides a method for removing additives from a plating solution, wherein 10 g of the adsorption resin prepared in Example 3 is filled into an adsorption column, 10 L of the plating solution is circulated through the adsorption column, and when the content of the additive in the plating solution is detected by HPLC and is lower than a maximum value, the circulation is stopped, the plating solution from which the additive has been removed is collected, the adsorption column is taken out, and the adsorption resin after adsorption is regenerated and recycled.
[0103] Example 5
[0104] This embodiment provides a method for regenerating an adsorption resin. The adsorption resin after adsorption in Example 4 is added to a treatment solution, compressed air is introduced into the solution with a ventilation volume of 15 mL / min, and at the same time, 1500 W ultrasonic treatment is performed for 1 hour, followed by filtration, washing, and drying to obtain a regenerated adsorption resin.
[0105] The treatment solution is an ethanol aqueous solution containing 10 wt % hydrochloric acid, wherein the ethanol content is 50 wt %.
[0106] Example 6
[0107] This embodiment provides a method for regenerating an adsorption resin. The adsorption resin after adsorption in Example 4 is added to a treatment solution, compressed air is introduced into the solution with a ventilation volume of 15 mL / min, and at the same time, 1500 W ultrasonic treatment is performed for 1 hour, followed by filtration, washing, and drying to obtain a regenerated adsorption resin.
[0108] The treatment solution is an ethanol aqueous solution containing 10 wt % NaOH, wherein the ethanol content is 50 wt %.
[0109] Test Example 3
[0110] The regenerated adsorption resins in Examples 5 and 6 were characterized using an ASAP2010 N2 physical adsorption instrument (Micromeritics, USA). The results are shown in Table 3.
[0111] Table 3
[0112]
[0113] It can be seen from the above table that the adsorption resin after regeneration still has a high specific surface area and rich pore structure.
[0114] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an adsorption resin, characterized in that: The following steps are involved: S1. Modification of activated carbon: After ball-milling the activated carbon, adding it to ethanol, adding long-chain silane, heating and stirring to react, filtering, washing, and drying to obtain modified activated carbon; S2. Low-crosslinked resin embedded activated carbon: the modified activated carbon obtained in step S1, styrene, divinylbenzene, toluene, porogen and initiator are mixed evenly to obtain an oil phase, gelatin and methylene blue are added to water to obtain an aqueous phase; under the protection of inert gas, the oil phase is added to the aqueous phase, heated and stirred to react, filtered, washed and dried to obtain low-crosslinked styrene-styrene copolymer embedded activated carbon; S3 chlorination: chloromethyl ether and the low cross-linked styrene - diphenylethylene copolymer embedded activated carbon prepared in step S2 were added to dichloromethane, zinc chloride catalyst was added, the reaction was heated with stirring, filtered, washed, and dried to obtain a chlorinated low cross-linked styrene - diphenylethylene copolymer embedded activated carbon; S4 complex cross-linking: The chlorinated low cross-linked styrene - diphenylethylene copolymer embedded activated carbon prepared in step S3 was added to ethylene dichloride, a catalyst ferric chloride was added, the reaction was heated with stirring, filtered, washed, and dried to obtain a highly cross-linked styrene - diphenylethylene copolymer embedded activated carbon; S5. Ultra-high crosslinking: The highly crosslinked styrene-stilbene copolymer-embedded activated carbon prepared in step S4 is added to ethylene dichloride, chloromethyl ether is added, fully swollen, cooled, tin tetrachloride catalyst is added, heat-insulated, heated for crosslinking reaction, and an adsorption resin is prepared.
2. The preparation method according to claim 1, characterized in that: The ball milling time in step S1 is 1-3h, the mass ratio of the activated carbon and the long-chain silane is 10:2-3, the long-chain silane is selected from at least one of hexadecyltrimethoxysilane, n-decyltrimethoxysilane, dodecyltrimethoxysilane, and dodecylmethyldimethoxysilane, and the temperature of the heating and stirring reaction is 35-45°C and the time is 2-3h.
3. The preparation method according to claim 1, characterized in that: The mass ratio of the modified activated carbon, styrene, divinylbenzene, toluene, porogen and initiator in step S2 is 10:4-6:5-7:10-12:0.2-0.3:0.01-0.02, the mass ratio of gelatin and methylene blue is 2-4:0.01-0.02, and the heating and stirring reaction method is: keeping warm and stirring the reaction at 70-80°C for 2-3h, keeping warm and stirring the reaction at 80-90°C for 4-6h, and keeping warm and stirring the reaction at 90-100°C for 3-5h.
4. The preparation method according to claim 1, characterized in that: In step S3, the mass ratio of chloromethyl ether, low-crosslinked styrene-styrene copolymer embedded activated carbon, and catalyst zinc chloride is 1.8-2.5:10:0.01-0.02, and the temperature of the heating and stirring reaction is 30-40° C. and the time is 3-5 hours.
5. The preparation method according to claim 1, characterized in that: In step S4, the mass ratio of the chlorinated low-crosslinked styrene-stilbene copolymer embedded activated carbon to the catalyst ferric chloride is 100:0.5-1, and the stirring reaction time is 5-7h.
6. The preparation method according to claim 1, characterized in that: In step S5, the mass ratio of the highly cross-linked styrene-styrene copolymer embedded activated carbon, chloromethyl ether, and catalyst tin tetrachloride is 20-30:3-4:0.01-0.02, the cooling to 4-8°C, the swelling time is 1-3h, the insulation treatment time is 0.5-1.5h, the temperature of the heating cross-linking reaction is 75-85°C, and the time is 10-12h.
7. An adsorption resin obtained by the preparation method according to any one of claims 1 to 6.
8. A method for removing additives from a plating solution, characterized in that: The adsorption resin described in claim 7 is filled into the adsorption column, and the plating solution is circulated through the adsorption column. When the content of additives in the plating solution is detected to be lower than the maximum value, the circulation is stopped, the plating solution with the additives removed is collected, the adsorption column is taken out, and the adsorption resin after adsorption is regenerated and recycled.
9. A method for regenerating an adsorption resin, characterized in that: The adsorbent resin after adsorption as claimed in claim 8 is added to the treatment solution, compressed air is introduced into the solution, and ultrasonic treatment, filtration, washing and drying are performed at the same time to obtain the regenerated adsorbent resin.
10. The regeneration method according to claim 9, characterized in that: The treatment solution is an ethanol aqueous solution containing 8-10wt% hydrochloric acid or NaOH, wherein the ethanol content is 40-60wt%, the ventilation volume of the compressed air is 10-20mL / min, the power of the ultrasonic treatment is 1000-2000W, and the time is 0.5-1.5h.
Citation Information
Patent Citations
Suspension polymerization preparation method of polystyrene / silica hydrated particle
CN103059181A
Preparation method for resin adsorbent compounded with straw activated carbon
CN104841387A